Contribution and role of UGEC project. Issue 1 (2nd January 2018) - Simon, David; Griffith, Corrie; Sánchez-Rodríguez, Roberto
ABSTRACT: This paper provides a brief history of the Urbanization and Global Environmental Change (UGEC) core project of the erstwhile International Human Dimensions Programme on GEC and the evolution of the science it supported and advanced from 2006 to 2017. This paper arises out of its synthesis phase, which concluded by planning the transition into an urban component of Future Earth. This legacy is vital in the context of our now predominantly urban planet and the associated flowering of urban research and related policy initiatives. The paper also analyses UGEC's role and contribution as a global science coordination (networking) project and, on this basis, offers guidance and future research suggestions for the urbanization and environmental change community.